2016
DOI: 10.1097/mib.0000000000000708
|View full text |Cite
|
Sign up to set email alerts
|

Fermentable Carbohydrate Restriction (Low FODMAP Diet) in Clinical Practice Improves Functional Gastrointestinal Symptoms in Patients with Inflammatory Bowel Disease

Abstract: The low FODMAP diet delivered in routine clinical practice seems effective in improving satisfaction with, and severity of, FGS in IBD. Randomized controlled trials are warranted to definitively establish effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
104
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(113 citation statements)
references
References 48 publications
0
104
0
7
Order By: Relevance
“…Recent studies with IBD patients with gastrointestinal symptoms showed a significant symptom relief under low FODMAP diet [39,41]. The evaluation of the daily sugar consumption revealed higher amounts in our IBD patients compared to healthy controls providing a potential explanation for gastrointestinal symptoms in some of these patients.…”
Section: Food Group Hc Total Ibd Ibd (Intake In [G/d]) CD Ucmentioning
confidence: 52%
See 2 more Smart Citations
“…Recent studies with IBD patients with gastrointestinal symptoms showed a significant symptom relief under low FODMAP diet [39,41]. The evaluation of the daily sugar consumption revealed higher amounts in our IBD patients compared to healthy controls providing a potential explanation for gastrointestinal symptoms in some of these patients.…”
Section: Food Group Hc Total Ibd Ibd (Intake In [G/d]) CD Ucmentioning
confidence: 52%
“…According to the BMI-classification of the World Health Organization (WHO), a BMI less than 18.5 kg/m² was considered as underweight, between 18.5 kg/m² to 25.0 kg/m² as normal weight, between 25.0 kg/ m² to 30.0 kg/m² as overweight (pre-obese) and over 30.0 kg/m² as obese [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Nutritional Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to different dietary interventions that have been assessed, their effectiveness has not been conclusively corroborated in spite of being a readily accessible and easy to implement option, which makes their use feasible in all healthcare centers, either alone or in combination with other measures for the reduction of this toxicity [17][18][19][20] . Based on the lack of conclusive evidence on GI toxicity reduction with nutritional interventions using the modification of a single dietary element in radiotherapy treated patients, the advantage of the low fructose, fermentable oligosaccharides, disaccharides, monosaccharides and polyols (FODMAP) diet lies in its intervention on multiple factors that influence radiation-induced enteropathy such as vowel motility regulation, lactose and osmotic agents restriction, and bacterial flora modification 9,21,22 , together with an improvement observed in abdominal symptoms of patients with inflammatory bowel disease, which has similarities with radiation-induced damage in its pathogenesis, and reported high compliance [23][24][25][26][27] . This is why assessment of this type of nutritional intervention is necessary in EBRT-treated patients in order to improve treatment tolerance and in this way positively influence patients' oncologic outcomes and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…En cuanto a las diferentes intervenciones dietéticas evaluadas, no se ha corroborado su efectividad de manera concluyente a pesar de que son una opción de fácil acceso e implementación, por lo que se pueden utilizar en todos los centros de atención, solas o en combinación con las demás medidas para la disminución de esta toxicidad [17][18][19][20] . Basados en la falta de evidencia concluyente de la disminución de la toxicidad gastrointestinal con las intervenciones nutricionales que utilizan la modificación de un solo elemento dietético en pacientes tratados con radioterapia, la ventaja de la dieta baja en fructosa, olioles, disacáridos, monosacáridos y polioles (FODMAP) radica en su intervención en múltiples factores que influyen en la enteropatía por radiación, como la regulación de la motilidad intestinal, la restricción de lactosa y agentes osmóticos, y la modificación de la flora bacteriana 9,21,22 ; aunado a la mejoría observada en los síntomas abdominales de pacientes con enfermedad inflamatoria intestinal, la cual tiene similitudes con el daño inducido por radiación en su patogenia, y el alto cumplimiento reportado [23][24][25][26][27] . Es por esto que es necesaria la evaluación de este tipo de intervención nutricional en pacientes tratadas con teleterapia pélvica, con la finalidad de mejorar la tolerancia al tratamiento y de esta manera influir de manera positiva en los resultados oncológicos y en la calidad de vida de las pacientes.…”
Section: Introductionunclassified